2022
DOI: 10.3389/fonc.2021.770894
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pretreatment Controlling Nutritional Status Score for Patients With Pancreatic Cancer: A Meta-Analysis

Abstract: BackgroundPrevious studies have explored the prognostic value of the pretreatment Controlling Nutritional Status (CONUT) score of patients with pancreatic cancer. However, the results of those studies were inconsistent. We used meta-analysis to investigate the impact of the CONUT score on the prognosis for patients with pancreatic cancer.MethodsWe thoroughly searched the PubMed, Web of Science, Embase, and Cochrane Library databases for relevant articles from inception to November 19, 2021. Combined hazard rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…A recent meta-analysis with ∼2300 patients from seven studies found that high CONUT score (HR of 1.56) was able to predict OS in patients with PC. 55 Another meta-analysis 56 that included 14 studies of ∼3500 patients, found that low preoperative PNI was related to poor OS (HR 1.67) and RFS (HR 1.4) in PC patients who underwent curative resection without preoperative neoadjuvant treatment. 56 Xie et al conducted a meta-analysis with nine studies ( n = 2153 patients) and found that low GNRI was associated with poor OS in patients with gastrointestinal cancer (HR = 1.94) and a higher risk of complications (OR = 2.19).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis with ∼2300 patients from seven studies found that high CONUT score (HR of 1.56) was able to predict OS in patients with PC. 55 Another meta-analysis 56 that included 14 studies of ∼3500 patients, found that low preoperative PNI was related to poor OS (HR 1.67) and RFS (HR 1.4) in PC patients who underwent curative resection without preoperative neoadjuvant treatment. 56 Xie et al conducted a meta-analysis with nine studies ( n = 2153 patients) and found that low GNRI was associated with poor OS in patients with gastrointestinal cancer (HR = 1.94) and a higher risk of complications (OR = 2.19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these results were confirmed in another study: the MNA was recommended by Hu et al as the nutritional tool for patients with heart failure; however, they also highlighted the CONUT score as a predictor of overall mortality [ 19 ]. In the context of oncology, two recent metanalyses showed that a high CONUT score is associated with poor overall survival in patients with renal cell carcinoma, urothelial carcinoma, and pancreatic cancer [ 20 , 21 ]; furthermore, Peng et al demonstrated that a high CONUT score correlates with worse prognoses in patients with non-small cell lung cancer [ 22 ]. In this study, we found a higher risk of diagnosis of sepsis in subjects with a higher CONUT score.…”
Section: Discussionmentioning
confidence: 99%
“…All the elements of the CONUT score have been linked to a worse prognosis among patients. Particularly, hospitalized individuals with low serum albumin have been found to have an elevated death rate [ 20 , 24 , 25 ]. Thus, albumin blood concentrations could be considered a predictor of in-hospital complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a lot of studies have demonstrated that the nutritional status of the body is closely associated with disease progression and long-term survival of cancer patients. [14][15][16] Besides, some studies revealed that pretreatment…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a lot of studies have demonstrated that the nutritional status of the body is closely associated with disease progression and long-term survival of cancer patients. [14–16] Besides, some studies revealed that pretreatment skeletal muscle index (SMI) is significantly related to poor prognosis of cancer patients. [17–21] However, the association between pretreatment SMI and survival of pancreatic cancer patients remains unclear up to now.…”
Section: Introductionmentioning
confidence: 99%